Family futures: childhood and poverty in urban neighbourhoods - Power, Anne (Case studies on poverty, place and policy, 2011)
Family futures is about family life in areas of concentrated poverty and social problems where surrounding conditions make bringing up children more difficult and family life is more fraught and limited. This book is based on a longitudinal study of more than 200 families interviewed annually over the last decade. It answers three important questions in the works of families themselves: What challenges face families in poor areas? How are the challenges being met? Have government efforts helped or hindered progress over the past decade?--From cover, [p]. 4